IMPLEMENTASI KEBIJAKAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Refnadilla, Risqidastia; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Non-metallic and rock mineral taxes is tax on activities taking mineral not metal and rock, good from source natural in in and / or surface earth for utilized. In Batang Gansal sub-district, there are still some mining management companies that do not have IUP and have not achieved the target of non-metal mineral and rock tax revenue. So that affect the Original Regional Income (PAD). Therefore the Government of Indragiri Hulu District issued Regulation No. 62 of 2011 Regarding the Directive of Non-Metallic Mineral and Metal Tax Executor. The objective of this Regulation is to reduce the existence of illegal and unlicensed mining entrepreneurs, as well as guidelines for acts used by the apparatus in registration, calculation, collection, collection and control of mining companies operating in Indragiri Hulu District. This study aims to determine the Implementation of Non-Metallic Mineral and Stone Taxes in the District of Batang Gansal Indragiri Hulu Regency. In the theory of implementation model by Van Meter dan Van Horn, there are six influential variables in the implementation, namely: Standards and targets of policies, resources, inter-organizational relation, characteristics of implementing agents, socio-political and economic conditions, disposition of implementors.The research method used in this research is qualitative. With technique that is done by purposive sampling , to informant in this research. In this writing, the informants are Head of Regional Income Board of Indragiri Hulu Regency, Secretary of Regional Income Agency, Head of Registration, Data Collection, Calculation, and Mining. Then analyze the data and manage.Based on research and discussion that researchers do in the field, it was found that the implementation of non-metallic mineral and rock tax policy in Batang Gansal District Indragiri Hulu Regency has not been implemented maximally. This is because the various factors that influence the implementation of this policy is difficult to perform optimally.Keywords : Implementation, Non-Metallic Mineral and Stone Taxes, Batang Gansal